PHYSICOCHEMICAL AND MINERAL CONTENTS OF HONEY FROM DIFFERENT DISTRICTS OF BALOCHISTAN, PAKISTAN - R. Yasmeen; F. Behlil; H. Ayub; I. Hafeez; U. Jabeen; S. Rizwan; A. Mushtaq; F. Bashir; S. Afzal (Journal of Animal and Plant Sciences, 2023)
Current studies based on the determination of physicochemical properties and mineral content of natural honey samples collected from 14 districts (Barkhan, Chagi, Dera Bugti, Duki, Kachhi, Kharan, Qilla Abdullah, Kohlu, Lasbella, Lorali, Mach, Masky, Sibi and Zhob) of Balochistan, Pakistan. Among physicochemical properties the observed moisture (12.5-7.68%), Ash content (0.50-0.003%), pH (5.49-3.34), total acidity (65-17 meq/kg), Electrical conductivity (0.791-0.150 mS/cm) and colour (ranges dark amber to white). These values indicated that all collected samples meet well with national and international standards. For mineral content Atomic Absorption spectrophotometer is used to detect level of certain metals (Cd, Pb, Cr, Mn, Fe, Cu, Zn, Na, K, Ca, Mg) to detect the pollutions in the districts where sampling was done. However, the honey samples collected from Barkhan districts display best results among all. Principle component analysis (PCA) was applied to differentiate honey samples on the basis of on elemental composition. The results revealed that four groups were formed in which honey samples show correlation with elements.
Keywords: physiochemical properties; mineral composition; atomic absorption; natural honey; Balochistan